Fiqh istihalah: integration of science and Islamic law - Jamaludin, Mohammad Aizat; Ramli, Mohd Anuar; Mat Hashim, Dzulkifly; Ab Rahman, Suhaimi (Kulliyyah of Science, International Islamic University Malaysia, 2012)
Modern developments in information technology have helped the expansion of knowledge, and shaped various aspects of contemporary life, including art, architecture, engineering, agriculture and the food industry. This paper discusses the role of modern technology in the food industry, with emphasis on the activities of enhancing, redesigning and upgrading the quality of the food. It analyses the use of technology in determining the permissibility of certain foods in compliance with the Islamic concept of halal; and it examines the concept of fiqh istihalah and its applications in the food industry, focusing on issues relating to the use of alcohol and gelatine ingredients in food products.